Land suitability of seaweed farming in Minahasa Regency, North Sulawesi Province - Schaduw, Joshian N. W; Ngangi, Edwin L. A; Mudeng, Joppy D (AQUATIC SCIENCE & MANAGEMENT, 2013)
The success of seaweed cultivation is determined from the determination of the location. This is because the production and quality seaweed influenced by ecological factors including the condition of the substrate surface waters, water quality, climate, geographical bottom waters. Arakan villages in the District of South Minahasa regency become one of the centers of seaweed cultivation in the province of North Sulawesi. The specific objective of this study was obtained in the form of a map of suitability mapping seaweed cultivation areas; gathering data and information about the extent of the area, water capacity, area unit, and carrying water. The study was conducted in the waters of the village of Arakan, District Tatapaan, South Minahasa regency, North Sulawesi. When phase 3 study conducted every month from June to December in 2012. The analysis is based on space availability, suitability waters that support the cultivation of seaweed. Suitability space spatially waters using physical and chemical parameters of waters which is a prerequisite eligibility seaweed cultivation. Spatial observations by using a Geographic Information System (GIS) for the weights and scores in determining the suitability of land. Process is done through the preparation of spatial database and